Manfaat Ekonomi Pengrajin Anyaman Di Kampung Arborek Kecamatan Meosmansar Kabupaten Raja Ampat - Umalam, Serita Victoriana; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p08, 2018)
The purpose of this research is to know the benefits of tourism coast economy are felt directly by the local people in Meosmansar Subdistrict, Raja Ampat Regency. The case study taken from the local people of Arborek Village which is a tourism village that has hand-crafed in the form of woven hats and bags of leaf mats. The type of data in this study used qualitative data. The data sources used are primary data and secondary data. The data are collected through by observation, indepth interviews with the some of the interviewees and as well as documentation. The technique of determination of the informant used in this research is purposive sampling. The informants which is selected in this study are representative of the local government in this case the Tourism and Culture officer of Raja Ampat Regency as well as the local community whose doing business craftsmen woven hats and bags. The data are collected is analyzed using the concepts of economic benefits by Leiper. The results of this study found the presence of perceived economic benefit directly by the local communities from tourism sector. Keywords: Economic Benefit, Local Community, Plating Handcraft, Arborek Village